Normalization of Diplomatic Relations Between Saudi Arabia and Iran: A Rationality Analysis of Saudi Arabia’s Foreign Policy - Harsono, Raihan Nustra; Septifa Leiliano Ceria (Universitas Muhammadiyah Malang, 2024)
Saudi Arabia and Iran are prominent countries in the Middle East region. Both countries are engaged in ongoing conflict and competition for influence in the Middle East. In 2023, Saudi Arabia and Iran reached an agreement to restore diplomatic relations, effectively addressing a longstanding conflict. The emergence of this peace agreement is closely associated with China's role as a mediator, facilitated through discreet diplomatic efforts with both countries. The normalization of diplomatic relations between Saudi Arabia and Iran prompts inquiry into the foundations of this agreement, considering the extensive history of discord between the two countries and the persistent civil conflicts in Yemen and Lebanon. This article analyzes the rationality of Saudi Arabia's foreign policy through a literature review and qualitative analysis, employing Graham T. Allison's Rational Actor Model. The findings indicate that Saudi Arabia's choice to reestablish relations with Iran is a logical one. The selected option optimally aligns with Saudi Arabia's national interests, including the enhancement of regional security and influence, the promotion of economic stability, and the fortification of the country's global standing.